2019
DOI: 10.1158/0008-5472.can-19-0490
|View full text |Cite
|
Sign up to set email alerts
|

miR-450a Acts as a Tumor Suppressor in Ovarian Cancer by Regulating Energy Metabolism

Abstract: miR-450aGlutaminolysis Invasion ACO2 Glucose NADPH Lipids Amino acids Nucleic acids Signaling pathways associated with migration and invasion Glutamine Glycolysis Pyruvate Lactate ATP VIM Citric Acid Cycle Oxidative phosphorylation • TIMMDC1 • MT-ND2 • ATP5B Ovary miR-450a Secondary site miR-450a acts as a tumor suppressor in ovarian cancer by repressing genes from mitochondrial OxPhos complexes and the citric acid cycle, thus regulating energy metabolism.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 45 publications
1
41
0
1
Order By: Relevance
“…We noticed that the in vivo effects are more pronounced than the in vitro effects in bladder cancer. Several studies (35)(36)(37)(38) have shown a similar pattern. One of the possible reasons is that we used transient transfected bladder cancer cells for in vitro assays, whereas steady transfected bladder cancer cells were used for in vivo experiments.…”
Section: Discussionsupporting
confidence: 54%
“…We noticed that the in vivo effects are more pronounced than the in vitro effects in bladder cancer. Several studies (35)(36)(37)(38) have shown a similar pattern. One of the possible reasons is that we used transient transfected bladder cancer cells for in vitro assays, whereas steady transfected bladder cancer cells were used for in vivo experiments.…”
Section: Discussionsupporting
confidence: 54%
“…Besides, another study revealed that there were 17 differentially expressed miRNAs in metastatic OC, among which miR-21, miR-150, and miR-146a were upregulated in metastatic OC tumors [7]. Meanwhile, it was documented that miR-450a could restrain OC cell metastasis by targeting various mitochondrial mRNAs [8]. Moreover, the dysregulated miRNAs may act as novel oncogenes or anti-oncogenes in OC by regulating target genes [9].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, specific target analysis carried out in ovarian cancer cell lines revealed that ACO2 transcript is a potential direct target for miR-450a, which could explain the observed decrease in glutamate production and increase in glutamine consumption by miR-450a, since ACO2 converts citrate into isocitrate, regulating the Krebs cycle and glutaminolysis. Finally, overexpression of miR-450a induced a reduction in cell migration and invasion, while tumor growth was reduced in a murine xenograft model, suggesting that miR-450a acts as a tumor suppressor [106] ( Figure 2).…”
Section: Mir-450amentioning
confidence: 99%